2023
DOI: 10.1172/jci171097
|View full text |Cite
|
Sign up to set email alerts
|

Proviral location affects cognate peptide–induced virus production and immune recognition of HIV-1–infected T cell clones

Filippo Dragoni,
Abena K. Kwaa,
Caroline C. Traut
et al.

Abstract: BACKGROUND HIV-1–infected CD4 + T cells contribute to latent reservoir persistence by proliferating while avoiding immune recognition. Integration features of intact proviruses in elite controllers (ECs) and people on long-term therapy suggest that proviruses in specific chromosomal locations can evade immune surveillance. However, direct evidence of this mechanism is missing. METHODS In this case report, we characterized integration sites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 78 publications
3
9
0
Order By: Relevance
“…Even though T cell activation is a prerequisite for latency reversal 88 , our data suggest that there is some discordance between Ag-driven T cell responses and latency reversal. This observation is consistent with studies demonstrating that for some proviruses latency reversal was achieved only after multiple rounds of T cell activation 16,32 , and that other factors, such as proviral location, can further reduce viral expression despite T cell activation and proliferation 66 . In addition, we showed that higher infection frequency among Ag-responding cells resulted in higher HIV-1 expression upon cognate Ag and PMA/I stimulation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Even though T cell activation is a prerequisite for latency reversal 88 , our data suggest that there is some discordance between Ag-driven T cell responses and latency reversal. This observation is consistent with studies demonstrating that for some proviruses latency reversal was achieved only after multiple rounds of T cell activation 16,32 , and that other factors, such as proviral location, can further reduce viral expression despite T cell activation and proliferation 66 . In addition, we showed that higher infection frequency among Ag-responding cells resulted in higher HIV-1 expression upon cognate Ag and PMA/I stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…The latter finding was based on the QVOA, which relies on latency reversal with the mitogen phytohemagglutinin (PHA), raising the question of whether polyclonal activation with mitogens induced proviruses that would not be induced in vivo. Here, we extend the results from a recent case report 66 and show that Ag presented in a physiologic manner by autologous APCs can reverse latency and cause viral particle production, further supporting that even proviruses that have been selected during long-term ART can be reactivated and could contribute to viral rebound if ART is interrupted in the absence of exceptional immune control.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It has been observed that certain infected cells may have some survival advantages compared to uninfected cells based on integration site locations or other mechanisms 44,45,4750,85 . As a sensitivity analysis, we therefore added a positive “survival advantage” rate ζ i =1e-5 per day for a small fraction of HIV-infected clones f ζ =1/100.…”
Section: Resultsmentioning
confidence: 99%
“…The role of homeostatic proliferation in the maintenance of the reservoir is less clear. Factors related to provirus sequence 42,43 or integration site 26,27,37,44,45 may confer selective advantages or disadvantages to certain proviral clones and therefore contribute to the reservoir’s extraordinary clonality. While provirus integration into oncogenes is now thought to play only a minor role in reservoir clonal expansion 46 , there is evidence that integration into transcriptionally inactive heterochromatin may confer a survival advantage 44,4750 .…”
Section: Introductionmentioning
confidence: 99%